Study on usage of over the counter medication among college students in Telangana: a cross sectional study - Ganapa, Praveena; Jothula, Kishore Y. (International Journal Of Community Medicine And Public Health, 2019)
Background: The use of over the counter medications (OTC) has been reported to be on rise internationally. The OTC drug market in India currently ranks 11th in the global OTC market. Since Indian patients have a huge tendency of self-treatment, the Indian market is characterized by a huge demand for OTC drugs. Hence the current study is undertaken to know the practices of over the counter medication among college students. Methods: Institutional based cross sectional study carried out in Pharmacy College and all interested students were included with sample size of 141. Data was collected by interview method by using questionnaire. Results were presented in percentages using SPSS statistical package version 23. Results: Subjects were opting for the over the counter medication. Most common drugs dispensed were cough remedies (52.4%) followed by antibiotics (38.2%). Most (47.5%) common source of medication was parents. Conclusions: Majority of the students were opting for the over the counter medication and it is need of the hour to improve the knowledge regarding its adverse effects and about rationale use of drugs and drug resistance.